Evaluating anthropometric scaling of a generic adult model to represent pediatric shoulder strength - Dalman, M.; Liao, A.; Saul, K. R. (Journal of Biomechanics, 2022)
The structure of the developing musculoskeletal system during childhood and adolescence influences tissue loading and function. Anatomical features important for musculoskeletal loading such as muscle volume and limb proportion vary with age but limited available anatomical data for the developing limb makes predicting loads challenging. Our aim was to evaluate whether anthropometric scaling of an existing adult musculoskeletal upper limb model is sufficient to accurately represent pediatric strength. An adult upper limb model was scaled using two scale factors based on length features and max isometric force (MIF). Length features (e.g. limb and muscle length) were scaled based on linear regression for available literature reports of forearm length vs. height (N = 366 Pediatric, N = 107 Adults), while MIF was scaled based on relating body mass vs. total shoulder muscle volume (N = 6). Children-specific models were developed for 6 pediatric individuals whose height, body mass, and shoulder moment-generating capacity (a common measure of strength) were previously reported. These models were used to predict isometric shoulder moments for flexion/extension, internal/external rotation, and ad/abduction and compared with physical measurements previously reported. The predicted isometric shoulder moments were significantly correlated to measured moments for these same individuals (p < 0.04, r2 > 0.7). However, predicted moments tended to underestimate measured values; shoulder external rotation was most accurately predicted (slope: 1.1234) while shoulder adduction was most underestimated (slope: 0.4624). This work provides an initial basis for pediatric scaling but illustrates the important need for additional direct measures of muscle size and limb strength and function in a pediatric population.